IMF policies for financial crises prevention in emerging markets - Lorenzo, Fernando (UN New YorkUS, 2006)
Reviews key items in the current debate about the new international financial architecture. Examines the policies for crisis prevention in emerging markets, analyzes them from the point of view of an international financial institution like the International Monetary Fund.